2018
DOI: 10.1155/2018/1542713
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Necessary Support Level for Oral Hygiene and Performance of Physical, Daily Activity, and Cognitive Functions

Abstract: To maintain good oral hygiene on their own, elderly adults need comprehensive abilities, such as physical, daily activity, and cognitive functions. In the long-term care certification, care support specialists conduct surveys that include a total of 74 items about physical function, daily activity function, living functions, cognitive function, mental/behavioral disorders, and adaption to social life. The data of the long-term care certification survey contain three items related to oral health: the necessary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Previous epidemiological studies have explored the relationship between dementia and oral health. Lee et al [ 7 ] reported that periodontitis is associated with a high risk of developing dementia, whereas Tamaki et al [ 8 ] indicated that oral hygiene is associated with cognitive function. Furthermore, certain studies showed that tooth loss is associated with the onset of dementia, particularly in the Japanese population [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous epidemiological studies have explored the relationship between dementia and oral health. Lee et al [ 7 ] reported that periodontitis is associated with a high risk of developing dementia, whereas Tamaki et al [ 8 ] indicated that oral hygiene is associated with cognitive function. Furthermore, certain studies showed that tooth loss is associated with the onset of dementia, particularly in the Japanese population [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the certification process for long-term care in Japan, the Needs Certification Committee conducts a survey of a total of 74 items, including physical function, cognitive function, life function, daily activity function, behavioral disorder, and adjustment to social life. The required level of care is classified into a total of 7 levels (support needs levels 1–2 and care needs levels 1–5) [ 22 ]. The data from the care certification survey include items associated with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Japanese individuals with long-term care needs are provided care services at home and in institutions [22] by municipalities [23]. The Municipal Needs Certification Committee is responsible for evaluating the requests for long-term nursing care by residents based on more than 70 functions, such as activities of daily living, cognitive function, physical function, living function, adaptation to society, and behavioral disorder [4,24]. The Municipal Care Certification Survey collects data related to the cognitive ability and dementia.…”
Section: Introductionmentioning
confidence: 99%